Effects of two teaching methods of connected speech in a Polish EFL classroom - Kul, Małgorzata (Research in Language, 2016)
Abe (2010) argues that the Negotiation of Form (NF) instruction exerts positive effects on learning of connected speech by Japanese learners of English, finding that the progres achieved with NF was more significant than for the traditional treatment. The study reported here seeks to uncover the acquisitional value of NF in a Polish classroom. The study hypothesizes that NF, in comparison with the deductive teaching method, effectively promotes learning of assimilation, elision and weak forms. The hypothesis was tested by investigating production and perception of 50 Polish students of English. As for evaluating the effects of the two types of instructions, a classic pretest-posttest design was used. With regard to methodology, acoustic analysis was performed. The results demonstrate that in general, NF proved more effective than NNF. With regard to individual processes of connected speech, NF was more effective in production, whereas no such effect was found for perception.